Study on the use of different glass fiber contents for self-compacting mortar - Nguyen, Thi Thu Huong (2021)
Glass Fiber-Reinforced Self-Compacting Mortar (GFRSCM) is a composite material consisting of a mortar of Portland cement and fine aggregate reinforced with alkali-resistant glass fibers. The properties of GFRSCM depend upon a wide range of variables including mix formulation, fiber type and content, length, orientation, and admixture used… In this paper, the authors intend to study the effect of glass fiber content on properties of GFRSCM at fresh and hardened state. The experimental results have shown that the more the content of glass fiber is used, the lower the resultant slump flow value of GFRSCM mixture. At hardened state, glass fiber content barely affects the compressive strength of GFRSCM. However, the higher the glass fiber content added, the greater flexural and splitting tensile strength is achieved. In terms of durable properties such as waterproof grade and abrasion resistance, glass fiber content does not influence on these properties. The outcomes of this study would be useful for further study on the application of the GFRSCM for the rehabilitation of some types of structures including civil engineering and hydraulic structures.